Acceleration of Aril Cracking by Ethylene in Torreya grandis During Nut Maturation - Gao, Yadi; Hu, Yuanyuan; Shen, Jiayi; Meng, Xuecheng; Suo, Jinwei; Zhang, Zuying; Song, Lili; Wu, Jiasheng (Frontiers in Plant Science, 2021)
Torreya grandis ‘Merrillii’ is a famous nut with great nutritional value and high medicinal value. Aril cracking is an important process for seed dispersal, which is also an indicator of seed maturation. However, the cracking mechanism of T. grandis aril during the maturation stage remains largely unknown. Here, we provided a comprehensive view of the physiological and molecular levels of aril cracking in T. grandis by systematically analyzing its anatomical structure, physiological parameters, and transcriptomic response during the cracking process. These results showed that the length of both epidermal and parenchymatous cell layers significantly increased from 133 to 144 days after seed protrusion (DASP), followed by a clear separation between parenchymatous cell layers and kernel, which was accompanied by a breakage between epidermal and parenchymatous cell layers. Moreover, analyses of cell wall composition showed that a significant degradation of cellular wall polysaccharides occurred during aril cracking. To examine the global gene expression changes in arils during the cracking process, the transcriptomes (96 and 141 DASP) were analyzed. KEGG pathway analysis of DEGs revealed that 4 of the top 10 enriched pathways were involved in cell wall modification and 2 pathways were related to ethylene biosynthesis and ethylene signal transduction. Furthermore, combining the analysis results of co-expression networks between different transcription factors, cell wall modification genes, and exogenous ethylene treatments suggested that the ethylene signal transcription factors (ERF11 and ERF1A) were involved in aril cracking of T. grandis by regulation of EXP and PME. Our findings provided new insights into the aril cracking trait in T. grandis.